(Briefly) living for politics: partisan independence and durability of the Portuguese governing elite - Carmo Duarte, Mariana (2021)
This article explores the influence of partisanship in the Portuguese governing elite’s durability from 1995 to 2015. Through a survival analysis, we studied the ministers and secretaries of State of seven governments. The main results suggest that partisanship is not relevant to explain the durability of ministers. Nevertheless, the independent Secretaries of State are less likely to remain on the office until the end of the mandate. Moreover, the effect of partisan independence on the durability of secretaries of States is larger amongst women and those aged between 41-50.